Anchoring effect in judgments of objective fact and subjective preference. (March 2021) - Andersson, Hanna; Bökman, Fredrik; Wallhagen, Marita; Holmgren, Mattias; Sörqvist, Patrik; Ahonen-Jonnarth, Ulla
Highlights: Effect of anchors on objective judgments and WTP regarding groceries. Eco-labels had an effect when judging a product's price but not when judging WTP. An interaction between anchor and eco-label was demonstrated in objective judgments. People with higher environmental concern was more sensitive to anchoring in WTP. Abstract: The way by which various sources of external information interact in their effects on judgment is rarely investigated. Here, we report two experiments that examine how two sources of external information—an anchor (a reference price) and an eco-label—influence judgments of an objective fact (product price) and a subjective preference (willingness-to-pay for the product). Participants' price judgments were drawn in the direction of the anchor point, whereas the eco-label resulted in higher judgments of objective fact (Experiment 1) but did not influence subjective preference (Experiment 2). Interestingly, the eco-label seemed to strengthen the effect of the high anchor in judgments of objective fact. Further, participants with higher environmental concern answered a higher price on the subjective preference questions when they received a high anchor, as well as a lower price when they received a low anchor in comparison to the low environmental concern group. This study demonstrates that various external information sources can strengthen each other's effects on consumer belief about products, while the effects are weaker for consumers' preferences. The implications of the results for decision making are discussed.